Acid Lactic Bacteria as a Bio-Preservant for Grape Pomace Beverage - Dias, Juliana Furtado; Simbras, Beatriz Duarte; Beres, Carolina; dos Santos, Karina Olbrich; Cabral, Lourdes Maria Correa; Miguel, Marco Antônio Lemos (Frontiers in Sustainable Food Systems, 2018)
A probiotized juice may be an advantage as it provides an alternative to probiotic dairy products. In addition, the use of agricultural residue to supplement a probiotic juice may be a solution for overproduction of this organic material. Many studies have been developed with fruit residues; however a definitive solution to this environmental problem has not yet been established. Therefore the objective of this study was to propose a probiotized juice using lactic bacteria that, besides functioning as starter culture, has a potential biopreservative action and provide suitable stability for the final product. A fermented beverage was formulated using commercial grape juice, Vitis vinifera Pinot noir grape pomace and lactic bacteria. Pathogenic strains were used to simulate a microbial contamination. The procedures were carried out according to the American Public Health Association and the results were expressed in media with standard deviation using statistical analyses performed by Prism. Lactic bacteria showed a cell growth around 4 log CFU/ml. There was a significant decrease in pH values (p < 0.05) when pure grape juice was fermented. The grape juice supplemented with grape pomace from white winemaking was able to induce a higher growth of lactic bacteria population during fermentation, around 1 log cycle CFU/mL, comparing to juice without supplementation. The beverage containing grape juice, water and pomace also presented growth on lactic bacteria population but Lactobacillus rhamnosus reached a higher concentration, of approximately 108 CFU/ml after 12 hour of fermentation. This was also observed when beverages were stored, only L. rhamnosus remained viable for ten days at 10oC. For all beverage samples contaminated with pathogens, the lactic bacteria population remained around 2 log CFU/g above the added pathogen population, and the final probiotic population was above 108 CFU/mL, but L. rhamnosus wasn`t able to reduce significantly pathogenic strains, however a bacteriostatic effect was observed. A probiotic grape juice supplemented with pomace was produced with viable probiotic cell during 12 hours fermentation and stored for 10 days under refrigeration temperature. And a potential bacteriostatic effect against food pathogens was observed.